Updates in chronic cholestatic liver diseases: Indian expert recommendations for diagnosing and managing complex cases - Wadhawan, Manav (International Journal of Research in Medical Sciences, 2025)
Cholestatic liver diseases (CCLDs) encompass hepatobiliary disorders leading to impaired bile secretion or reduced production, causing liver damage and fibrosis. Diagnosis relies on differentiation between hepatocellular and cholestatic diseases based on liver function tests (LFTs). Histological testing aids in detecting cholestasis-related alterations, crucial for identifying conditions like primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC). Non-invasive tests like FIB-4 and aspartate transaminase to platelet count ratio index (APRI), nonalcoholic fatty liver disease (NAFLD) fibrosis scoring, and elastography, offer alternatives to liver biopsy for fibrosis assessment. Evolving diagnostic procedures, such as endoscopic ultrasound-guided biopsies, complement traditional methods. Chronic cholestatic liver disease management includes treatment with ursodeoxycholic acid (UDCA). Alcoholic liver disease requires abstinence and nutrition therapy, while NAFLD management involves lifestyle changes and medications. Drug-induced liver injury necessitates prompt discontinuation and may involve UDCA, corticosteroids, and targeted therapies. Emerging treatments include farnesoid X receptor agonists, peroxisome proliferator-activated receptor agonists, fibroblast growth factor 19 agonists, and immunosuppressive agents for conditions like PSC and nonalcoholic steatohepatitis. Ongoing evaluations explore various drug classes with newer therapeutic targets for these liver conditions.